Healthy Living for Elders: Scrambling for the Best Foods - Paulina Wittkowsky (EDIS)
Unscramble the words in this document to spell some of the foods that are best for good health. Then, write down each of the numbered letters on the blanks to figure out the message! This is document FCS8615-ENG, one in a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL 32611. Publication date: March 2004.